Coexistent subclinical hypothyroidism is associated with an increased risk of new cardiovascular events in rheumatoid arthritis: an explorative study. (2nd November 2021) - Agca, R; Heslinga, M; Raterman, HG; Simsek, S; Voskuyl, AE; Nurmohamed, MT
Abstract : Objective : Autoimmune thyroid disease often coexists with rheumatoid arthritis (RA) and is associated with elevated cardiovascular (CV) risk. However, studies in RA patients are scarce. Our aim was to investigate whether autoimmune thyroid disease increases the risk of new cardiovascular disease (CVD) in RA. Method : Thyroid-stimulating hormone (TSH) and serum free thyroxine (FT4) were assessed in 323 RA patients participating in an ongoing prospective cohort study designed to assess CV risk factors, morbidity, and mortality. Cox proportional hazard models were used to calculate hazard ratios (HRs) for new CVD and adjusted for age, gender, smoking, prevalent CVD, thyroxine replacement therapy, and RA duration. Results : Of the 323 participants, 65.3% were female, and mean ± sd age was 63 ± 7 years. At baseline, 8.1% were hypothyroid (n = 26, 16 clinical, 10 subclinical), 6.8% hyperthyroid (n = 22, 13 clinical, 9 subclinical), and 85.1% (n = 275) euthyroid. A new CV event developed in 94 patients (29.1%) during follow-up. Compared to euthyroid patients, the HR adjusted for age, gender, and prevalent CVD was 2.83 [95% confidence interval (CI) 1.13–7.09; p = 0.026] for subclinical hypothyroidism. Further adjustment for smoking, thyroxine replacement therapy, and RA duration resulted in an HR of 3.0 (95% CI 1.19–7.54; p = 0.02) for CV events in patients with subclinical hypothyroidism. Conclusion : There was no difference in CVD between RA patients with hypothyroidism and hyperthyroidism versus euthyroid patients. Coexistence of subclinical hypothyroidism with RA is associated with a higher occurrence of new CV events. Treatment trials are needed to determine whether thyroxine supplementation can further improve CV outcome in these patients.